A Feminist Analysis of Katy Perry’s “Woman’s World” Lyrics and Music Video - Rafita Prasetya Ningsih; Krisna Sujiwa (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2026)
Music videos and song lyrics function as cultural texts through which gender ideologies are both reinforced and contested. Despite growing interest in feminist media studies, few studies have integrated lyrical and visual analysis of contemporary pop music using Simone de Beauvoir's foundational concept of women as